Effect of olive fruit fly infestation on the quality of olive oil from cultivars cobrançosa, madural and verdeal transmontana - Pereira, J.A. (2004)
Olives (Olea europaea L.) from cultivars Cobrançosa, Madural and Verdeal Transmontana were collected separately and divided into two different groups according to the presence or absence of infestation by the olive fruit fly (Bactrocera oleae Gmel.). These two groups were then mixed in varying percentages to create five groups of olives per cultivar with infestation levels: 0, 12.5, 25, 50 and 100%. Each group was then processed to produce olive oil. The results, regarding mainly acidity, peroxide value, and stability to oxidation, suggest that olive fruit fly infestation reduces the quality of the olive oil. The effects of infestation varied according to cultivar, but in general the total tocopherol content was always lower at the 100% infestation level. The oil from cultivar Verdeal Transmontana had the lowest tocopherol content compared to oil from cultivars Cobrançosa and Madural, which could explain the lower quality of its oil.